1999
DOI: 10.1046/j.1440-1754.1999.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein B deficiency: Clinical, histological and molecular evaluation

Abstract: Congenital alveolar proteinosis due to surfactant protein B deficiency is an inherited disease which results in severe respiratory failure in term infants soon after birth. The pathophysiologic basis of this disease is now known to be an inability to synthesise adequate quantities of normally functioning surfactant protein B. We report a male infant with fatal respiratory failure of neonatal onset, and histopathological features typical of those seen in congenital alveolar proteinosis. Molecular analysis of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Sequence changes (mutations, polymorphisms, and other variants) are indicated upon their location on the gene according to the recommendations for a nomenclature for human gene mutation, [Antonarakis and the Nomenclature Working Group, 1998], 1970insdel(CA) n indicating the intron-4 compound insertiondeletion polymorphism. References between parentheses: a, Lin et al [2000]; b, Nogee et al [2000]; c, Tredano et al [1999]; d, this manuscript; e, Lin et al [1998]; f, Nogee et al [1994]; g, Somaschini et al [2000]; h, Tredano et al [1998]; i, Floros et al [1995]; j, Williams et al [1999]; k, Klein et al [1998]; l, Dunbar et al [2000]; m, Ballard et al [1995]; n, Weaver and Conkright [2001]; o, Pilot-Matias et al [1989]. the samples were lipid extracted, the lower phase was Folch washed, and the phospholipid content was assessed from inorganic phosphate of the lipid extracts.…”
Section: Surfactant Protein Characterizationmentioning
confidence: 99%
“…Sequence changes (mutations, polymorphisms, and other variants) are indicated upon their location on the gene according to the recommendations for a nomenclature for human gene mutation, [Antonarakis and the Nomenclature Working Group, 1998], 1970insdel(CA) n indicating the intron-4 compound insertiondeletion polymorphism. References between parentheses: a, Lin et al [2000]; b, Nogee et al [2000]; c, Tredano et al [1999]; d, this manuscript; e, Lin et al [1998]; f, Nogee et al [1994]; g, Somaschini et al [2000]; h, Tredano et al [1998]; i, Floros et al [1995]; j, Williams et al [1999]; k, Klein et al [1998]; l, Dunbar et al [2000]; m, Ballard et al [1995]; n, Weaver and Conkright [2001]; o, Pilot-Matias et al [1989]. the samples were lipid extracted, the lower phase was Folch washed, and the phospholipid content was assessed from inorganic phosphate of the lipid extracts.…”
Section: Surfactant Protein Characterizationmentioning
confidence: 99%
“…First, it reduces surface tension at the air-liquid interface of the lung. This function requires an appropriate mix of surfactant lipids and the hydrophobic proteins, SP-B and SP-C [9]; SP-B deficiencies have been associated with infant mortality due to respiratory distress syndrome [10,11]. Second, surfactant also plays a role in host defense against infection and inflammation.…”
mentioning
confidence: 99%
“…Thus, surfactant extracts containing only SP-B reached significantly lower surface tension in contrast to SP-C containing surfactant extracts. Studies on SP-B gene knockout mice, as well as infants with SP-B deficiency, have demonstrated an incompatibility with life as a result of dysfunctional surfactant action [30,31]. In addition, SP-B has been shown to demonstrate antimicrobial activity, suggesting that pulmonary host defence may involve an interaction between SP-A, -D and -B.…”
Section: Biochemical Background Of Surfactant Analoguesmentioning
confidence: 99%